Structure‐Activity Relationship of Phenylpyrazolones against Trypanosoma cruzi. (27th April 2020) - Sijm, Maarten; Sterk, Geert Jan; Caljon, Guy; Maes, Louis; de Esch, Iwan J. P.; Leurs, Rob
Abstract: Chagas disease is a neglected parasitic disease caused by the parasitic protozoan Trypanosoma cruzi and currently affects around 8 million people. Previously, 2‐isopropyl‐5‐(4‐methoxy‐3‐(pyridin‐3‐yl)phenyl)‐4, 4‐dimethyl‐2, 4‐dihydro‐3 H ‐pyrazol‐3‐one (NPD‐0227) was discovered to be a sub‐micromolar inhibitor (pIC50 =6.4) of T. cruzi . So far, SAR investigations of this scaffold have focused on the alkoxy substituent, the pyrazolone nitrogen substituent and the aromatic substituent of the core phenylpyrazolone. In this study, modifications of the phenyldihydropyrazolone scaffold are described. Variations were introduced by installing different substituents on the phenyl core, modifying the geminal dimethyl and installing various bio‐isosteres of the dihydropyrazolone group. The anti T. cruzi activity of NPD‐0227 could not be surpassed as the most potent compounds show pIC50 values of around 6.3. However, valuable additional SAR data for this interesting scaffold was obtained, and the data suggest that a scaffold hop is feasible as the pyrazolone moiety can be replaced by a oxazole or oxadiazole with minimal loss of activity. Abstract : Testing the scaffold : A series of phenylpyrazolones has been investigated to find compounds that are active against T. cruzi . Although none could match the activity of NPD‐0227 (pIC50 =6.4), the SAR study turned up valuable data for hit‐to‐lead optimization and improving the selectivity index, such as the possibility of replacing the pyrazolone moiety by an oxazole or oxadiazole.